The effect of Latin dance on social physique anxiety in middle school girls: a pilot study - Liu, Xutao; Wei, Xiaozhuo; Soh, Kim Geok; Lu, Yingjie; Li, Rongzhi (Frontiers in Public Health, 2025)
IntroductionSocial physique anxiety (SPA) is a prevalent psychological issue among adolescents, particularly among female middle school students. SPA is characterized by fear of negative evaluation based on physical appearance and can significantly impact self-esteem and social interactions. This study aimed to investigate the effects of a 4-week Latin dance intervention on reducing SPA in middle school girls.MethodsA total of 40 female middle school students were randomly assigned to either the experimental group (n = 20) or the control group (n = 20). The experimental group participated in Latin dance training, consisting of two 40-minute sessions per week for four weeks. The control group engaged in traditional physical education classes, focusing on basketball. SPA was measured using the Social Physique Anxiety Scale (SPAS) before and after the intervention, assessing three dimensions: Negative Evaluation (NE), Self-performance (SP), and Social Comparison (SC).ResultsThe results indicated that the Latin dance intervention significantly reduced SPA across all three dimensions, with the most significant improvements observed in NE and SP (p < 0.05). The experimental group showed greater reductions in SPA compared to the control group (p = 0.004).DiscussionThese findings suggest that Latin dance is an effective intervention for reducing SPA in adolescents. The improvements in SPA, particularly in NE and SP, highlight the potential of Latin dance to promote positive body image and enhance self-esteem. This study contributes to the growing body of research on the mental health benefits of dance and provides insights into integrating physical activity into psychological interventions aimed at improving adolescent well-being.